2010
DOI: 10.1038/cr.2010.116
|View full text |Cite
|
Sign up to set email alerts
|

VEGFR-3 ligand-binding and kinase activity are required for lymphangiogenesis but not for angiogenesis

Abstract: Although VEGFR-3 deficiency disrupts blood vascular development during early embryogenesis, the underlying mechanism was not clear. To characterize its function in angiogenesis and lymphangiogenesis, we employed two genetically modified mouse models in this study, targeting the coding region for the ligand-binding domain (Vegfr3 ∆LBD ) or the tyrosine kinase domain with an inactivation point mutation (Vegfr3 TKmut ). We show that lymphatic growth was disrupted in Vegfr3 ∆LBD/∆LBD and Vegfr3 TKmut/TKmut mice, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
97
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 125 publications
(101 citation statements)
references
References 43 publications
1
97
0
3
Order By: Relevance
“…Consistently, similar phenotypes were also observed in an independent mutant mouse model in which the kinase activity of VEGFR-3 was ablated by a missense mutation in the tyrosine kinase catalytic domain. Blood vascular development proceeded normally while lymphangiogenesis was disrupted in Vegfr3 TKmut/TKmut mice (Zhang, Zhou et al 2010). Interestingly, in Vegfr3 ΔLBD/ΔLBD mice, lymph sac formation occurred but without lymphatic vessel sprouting due to the loss of ligand sensing ability by LEC expressing the truncated VEGFR-3 (VEGFR-3 ΔLBD ).…”
Section: Expansion Of Lymphatic Vesselsmentioning
confidence: 99%
See 3 more Smart Citations
“…Consistently, similar phenotypes were also observed in an independent mutant mouse model in which the kinase activity of VEGFR-3 was ablated by a missense mutation in the tyrosine kinase catalytic domain. Blood vascular development proceeded normally while lymphangiogenesis was disrupted in Vegfr3 TKmut/TKmut mice (Zhang, Zhou et al 2010). Interestingly, in Vegfr3 ΔLBD/ΔLBD mice, lymph sac formation occurred but without lymphatic vessel sprouting due to the loss of ligand sensing ability by LEC expressing the truncated VEGFR-3 (VEGFR-3 ΔLBD ).…”
Section: Expansion Of Lymphatic Vesselsmentioning
confidence: 99%
“…It is also crucial for pathological lymphangiogenesis, such as in tumor (He et al 2004a;He et al 2005). While VEGFR-3 is initially expressed by all the endothelial cells of primary vascular network in mice during the embryonic development, its expression is primarily in LECs at the later stage of embryogenesis and persists in adult lymphatic vessels (Kaipainen et al 1995;Zhang, Zhou et al 2010). It has been found that TBX-1 activates VEGFR-3 transcription in endothelial cells (ECs) by binding to an enhancer element in the Vegfr3 gene .…”
Section: Expansion Of Lymphatic Vesselsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this situation, and in contrast to FLT-1, signaling mediated through FLT4 does not require activation by any of its recognized ligands, VEGFB or VEGFC. 30 Finally, FLT4 missense somatic mutations have been found in infantile hemangiomas, 31 further implicating this gene in the pathogenesis of pyogenic granuloma.…”
Section: Modern Pathology (2013) 26 247-255mentioning
confidence: 99%